An Analysis of Students' Ability in Writing Descriptive Paragraphs of Second Semester English Language Education of FKIP UIR - Nadila Mudea N; Estika Satriani (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2023)
This study aimed to know the second-semester students writing abilities in writing descriptive paragraphs. This is quantitative research. The populations were the second-semester students of the academic year 2018/2019. The total of students was 98 students. The populations were the second-semester students of the academic year 2018/2019. The total of students was 98 students. To minimize or to get the sample, the researcher applied two techniques. First, the researcher decided on the class; it used simple random sampling and quota sampling techniques. The documents were used as the main data of this study. Therefore, the finding showed that the second-semester students' abilities in writing descriptive paragraph were good. It can be seen there were 62% of students belonged to a good category, 33% of students belonged to the excellent category, and 3% of students belonged to the average category. Based on this aspect, the students had a problem with using grammar and sentence structure (18%), but they understood how to connect their paragraphs with the topics by called content (22%). In fact, there was no significant difference in score between both, so it means that the second-semester student at English Language education-UIR in writing descriptive paragraphs was good.